ANALISIS FRAMING BERITA KPK VERSUS POLRI DI SURAT KABAR MEDIA INDONESIA DAN JAWA POS - Nasifah, Khoirun; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The newspaper of Media Indonesia and Jawa Pos are national media that each has a different point of view in the way of preaching the chaotic The Corruption Eradication Commission KPK and The Police Of Republic Of Indonesia (POLRI). This news was a result of the construction of the two media are framed differently according the editorial policy and viewpoints of both media. To that end, the matter was examined how the news framing of Media Indonesia and Jawa Pos newspaper on KPK versus POLRIduring the period from 23 January to 27 January 2015 2015. This research aims to find out how the framing the proclamation of Media Indonesia Jawa Pos newspaper on the KPK versus POLRI case. As well as to know the ideological representation of the Annunciation KPK versus POLRI in both newspapers.The methods used in this study is a qualitative method of faminganalysis approach. In data collection, researchers using the technique of documentation and interviews. After the data was collected, then the researchers analyzed by using four basic elements framing expressed by Zhongdang Pan and Gerald M Kosicki. The subject of the research is composed of journalists and Media Indonesia and Java Postredakctional devices. The objects in this research is the news of KPKversus POLRI in the Media Indonesia and Jawa Post newspaperJanuary 23, 2015 until January 27, 2015 edition.The results showed that; First, the Jawa Pos framing the KPK leader reporting as swept up as the establishment candidate's Assistant Budi Gunawan as a suspect by the KPK, so reporting the leadership of KPK was a form of criminalization. While the Media Indonesia framing reporting leader KPK as a regular legal process, public speculation that the reporting done because the ' revenge ' Police to the KPK was incorrect. Second, the Jawa Pos in the proclamation of the chaotic KPK-POLRI do alignments against the KPK. Alignments being performed related ideology of Jawa Pos that looks at the institutions of the KPK as most institutions 'clean'. While the ideology of the Media Indonesia in framing news KPK versus POLRI was represented with emphasis on aspects of the law being used in news coverage.Keywords: Framing analysis, news, newspaper